Fracture strength and toughness of chemical-vapor-deposited polycrystalline diamond films. Issue 15 (15th October 2018) - An, Kang; Chen, Liangxian; Yan, Xiongbo; Jia, Xin; Liu, Jinlong; Wei, Junjun; Zhang, Yuefei; Lu, Fanxiu; Li, Chengming
Abstract: The strength of diamond films prepared by chemical vapor deposition (CVD) is usually much lower than that of natural-type IIa single-crystal diamonds. In this work, the fracture strength of free-standing diamond films deposited by direct current arc plasma jet CVD has been examined by conducting three-point bending experiments. The results obtained for both the polished and as-grown samples were in good agreement with a well-known Hall–Petch equation describing the relationship between the fracture strength and grain size, indicating that grain refinement represented an effective way of improving the mechanical properties of CVD diamond films. Furthermore, the diversification of the crystalline texture of the films achieved by polishing apparently increased their fracture strength, which was inversely proportional to the film thickness. A theoretical method for estimating the fracture strength of free-standing CVD diamond films by approximating their intrinsic strength was proposed, whereas their fracture toughness was determined by conducting simplified four-point bending tests at room temperature, 25 °C, using a single-edge pre-cracked beam method.